Crossing stones - Frost, Helen, 1949- (New York : Frances Foster Books, 2010)
In their own voices, four young people, Muriel, Frank, Emma, and Ollie, tell of their experiences during the first World War, as the boys enlist and are sent overseas, Emma finishes school, and Muriel fights for peace and women's suffrage.
"Frances Foster Books."
English language and literature.
Keywords: Novels in verse; World War, 1914-1918 -- Fiction; War -- Fiction; Soldiers -- Fiction; Friendship -- Fiction; Family life -- Fiction; Women -- Suffrage -- Fiction; Michigan -- History -- 20th century -- Fiction